Hubungan caring perawat terhadap tingkat kepuasan pasien closed fraktur di Instalasi Gawat Darurat RS X - Budi, Mei; Wijayanti, Novida Prima; Pangaribuan, Santa Maria; Purborini, Nurul (Borobudur Nursing Review, 2025)
Background: A fracture or broken bone is a total or partial loss of bone continuity, which is determined based on the type and extent. Based on data from nurses on duty at the IGD RS X, handling fracture patients remains problematic. One action nurses can take to improve patient satisfaction in health services is to demonstrate caring behaviour. Caring is a behaviour or action that genuinely provides others with a sense of physical and emotional security. Methods: This is a descriptive correlational study with a cross-sectional design. The sample consisted of 55 patients, selected using convenience sampling. Data collection used the nurse caring questionnaire and patient satisfaction questionnaire. The data analysis used in this study includes univariate and bivariate analyses. Results: Characteristics of respondents in the IGD RS X, based on gender: 54,5% were male; education level: 47,3% higher education; and occupation: 29,1% were civil servants. Most respondents were at the satisfaction level 90,0%. The results of the Spearman rank correlation test indicate a strong relationship between nurses' caring behaviour and patient satisfaction in the IGD RS X (P-value = 0.040).